Factores que inciden en la producción científica en estudiantes y bachilleres de medicina humana, facultad de medicina humana de la Universidad Nacional de la Amazonía Peruana durante los años 2020 al 2022 - Vasquez Ascate, Jhosephi Jhampier (2023)
Objectives. To determine the factors that influence the scientific production of students and graduates from the Faculty of Human Medicine at the National University of the Peruvian Amazon (UNAP) during the years 2020 to 2022. Materials and Methods. Descriptive cross-sectional study of medical students and graduates. Results. Showed that only 13.9% of the participants published scientific articles. The level of education and previous university education did not have a significant impact on the publication of articles, while subscribing to research journals and belonging to scientific societies were significantly associated with scientific publication (p<0.05). Other important factors included peer mentoring, availability of time, advanced knowledge in searching and writing scientific information, and institutional factors such as recognition within the university and access to research resources. Conclusions. The study highlights the importance of a series of personal, academic, and institutional factors for scientific production in students and graduates of Human Medicine at UNAP, such as participation in scientific activities, collaboration and support from peers and mentors, and recognition and support from the university are key factors to boost scientific production in this group of students.